Three‐Pronged Attack by Hybrid Nanoplatform Involving MXenes, Upconversion Nanoparticle and Aggregation‐Induced Emission Photosensitizer for Potent Cancer Theranostics. Issue 8 (3rd June 2022) - Wang, Yuanwei; Niu, Niu; Huang, Yang; Song, Shanliang; Tan, Hui; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract: Inspired by the excellent photothermal conversion ability and inherent nanomedicine platform property of MXenes, efficient reactive oxygen species production and prominent fluorescence emission feature of aggregation‐induced emission (AIE)‐active photosensitizers (PSs), as well as the extending excitation wavelength capability of upconversion nanoparticles (UCNPs), a versatile nanoplatform comprised of Ti3 C2 nanosheets (NSs), AIE‐active PSs and UCNPs is intelligently fabricated. This three‐pronged strategy takes advantages of each component simultaneously, and realizes fluorescence imaging/photoacoustic imaging/photothermal imaging triple‐modal imaging‐guided photothermal/photodynamic synergetic therapy under 808 nm laser irradiation. The introduction of UCNPs actualizes the long wavelength‐activation of AIE‐active PSs, which significantly increases the tissue penetration depth. Spatially isolation of AIE‐active PSs and Ti3 C2 NSs is beneficial for suppressing the fluorescence quenching effect of Ti3 C2 NSs, bringing about ultimately brilliant fluorescence. The covalently bonded polymer surface endows the nanoplatform with excellent physiological stability and efficient tumor accumulation. These outputs reveal a win‐win cooperation of multiple inorganic/organic nanocomposites for phototheranostics, and present great potential for future clinical translations. Abstract : A three‐pronged attack is explored by establishing a multifunctional nanoplatform comprised of an aggregation‐induced emission‐active photosensitizer, Ti3 C2 nanosheets, and upconversion nanoparticles. Fluorescence imaging/photoacoustic imaging/photothermal imaging triple‐modal imaging‐guided synergetic photothermal therapy/photodynamic therapy is realized for potent cancer theranostics, providing a blueprint for the next generation of anticancer therapeutics.